Female and LGBTQI+ students’ experiences of sexism and sexual harassment in Lisbon’s universities - Kärkinen, Juuli Annina (2021)
Sexism and sexual harassment are everyday problems in women’s and LGBTQI+ peoples’ lives. Academia hasn’t been spared from them, as it is an institution marked by hierarchies and different power dynamics. This master’s dissertation focuses on students’ experiences of sexism and sexual harassment in Lisbon’s universities. The target group was female and LGBTQI+ students and the data were gathered by online survey during March-August 2020. A feminist critical discourse analysis was used to analyse students’ experiences. Three main findings were made: (1) Students experience gendered discrimination and sexual harassment in various forms in their daily lives in academia, and the most common ones were verbal behaviours, such as diminishing female students, sexist comments and sexual remarks; (2) Students usually don’t report their experiences to universities, though they rather seek support from friends and try to warn them for similar events; (3) Students think that universities do not do enough to prevent and handle above mentioned events sufficiently. They wished for more serious consequences for perpetrators, better support systems and real attention for reports.